2022
DOI: 10.1177/00405175221094046
|View full text |Cite
|
Sign up to set email alerts
|

Study on color ink diffusion in fabrics and color reproduction of digital inkjet printing

Abstract: The accuracy of color reproduction of digital printed fabric is affected by fabric structural characteristics and treatment, and the adjustment of color management is required for reducing the color difference. To study the mechanism of color presenting, the interaction of ink droplets diffusing on polyester knitted fabric with different structures and treatment was investigated. The result showed that the smaller the porosity, the larger the diffusion area. Besides that, the pretreatment alleviated the edge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…With the original color management, the average color difference of the color checker was 20.834, and with the FPO method, the average color difference was 5.254, which indicated that the color difference was greatly reduced. Compared to the optimal color reproduction method proposed in related research, 11 which yielded an average color difference of 7.3, the color reproduction effect was further improved with the use of the FPO method.…”
Section: Evaluation Of the Effect Of The Fpo Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…With the original color management, the average color difference of the color checker was 20.834, and with the FPO method, the average color difference was 5.254, which indicated that the color difference was greatly reduced. Compared to the optimal color reproduction method proposed in related research, 11 which yielded an average color difference of 7.3, the color reproduction effect was further improved with the use of the FPO method.…”
Section: Evaluation Of the Effect Of The Fpo Methodsmentioning
confidence: 97%
“…For the yellow ink, the fitting equation is given in Equation (10), and the inflection point of the slope was at x ¼ 80:31, so the yellow ink limit was determined as 80% y ¼ 7E À 08x 3 À 0:00002x 2 þ 0:0015x À 0:0066; R 2 ¼ 0:9979 (10) The fitting equation of the black ink was obtained as given in Equation (11), and the inflection point of the slope was at x ¼ 133:33. Since the maximum ink output of the printing machine is 100%, the ink limit for black ink was set to 100%…”
Section: Determination Of the Optimal Single-channel Ink Limitmentioning
confidence: 99%
See 3 more Smart Citations